Funding Conservation through an Emerging Social Movement. (January 2020) - Freeling, Benjamin S.; Connell, Sean D.
Abstract : People will pay to protect our environment. To encourage donations, it is fundamental to understand the values that motivate people. Here, we identify a new opportunity to attract donations from an emerging social movement to deliver benefits to the natural world.